2014
DOI: 10.1111/tmi.12407
|View full text |Cite
|
Sign up to set email alerts
|

Clinical aspects of paediatric visceral leishmaniasis in North‐west Ethiopia

Abstract: Abstractobjective Visceral leishmaniasis (VL) in north-west Ethiopia is causing an overwhelming case load among adult migrant workers that masked the disease burden in children. This study describes the clinical profile and explores comorbidities in paediatric VL patients.methods A prospective study at two hospitals in this region (Gondar and Humera) was conducted in a year period, 2011-2012. The clinical manifestations and comorbidities such as malnutrition, intestinal parasitosis and vitamin D deficiency and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 48 publications
0
25
1
Order By: Relevance
“…Sensitivity analysis was carried out by excluding each study step-by-step from the metaanalysis and comparing point prevalence estimate before and after removing a single study. Accordingly, removing a single study did not alter the pooled prevalence estimate considerably, with sensitivity analysis ranging from 20.88% (when [26] was removed) and 24.86% (when [25] was removed) (Fig. 4).…”
Section: Sensitivity Analysismentioning
confidence: 95%
See 1 more Smart Citation
“…Sensitivity analysis was carried out by excluding each study step-by-step from the metaanalysis and comparing point prevalence estimate before and after removing a single study. Accordingly, removing a single study did not alter the pooled prevalence estimate considerably, with sensitivity analysis ranging from 20.88% (when [26] was removed) and 24.86% (when [25] was removed) (Fig. 4).…”
Section: Sensitivity Analysismentioning
confidence: 95%
“…Though the burden of HIV infection is diminishing in the general Ethiopian population, the prevalence of HIV infection in VL patient is considerably high [23,24]. According to various study reports on co-occurrence of HIV and VL in Ethiopia, the prevalence is considerably inconsistent and heterogeneous, ranging from 0.82% [25] to 67.5% [26]. Besides, to the best of our knowledge, there was no previous study that estimates the pooled prevalence of HIV coinfection in people infected with VL in Ethiopia; hence, this systematic review and meta-analysis was carried out.…”
Section: Introductionmentioning
confidence: 99%
“…Infection with Leishmania parasites can be asymptomatic or can manifest as a progressive disease. VL is characterised by hepatosplenomegaly, fever, weight loss, hyperglobulinemia and pancytopenia [ 6 ]; if left untreated, it is almost always fatal. In Ethiopia, VL is caused by L .…”
Section: Introductionmentioning
confidence: 99%
“…donovani and it is one of the most significant vector-borne diseases; Ethiopia has the second largest number of VL cases in sub-Saharan Africa with an estimated annual burden of 4500 to 5000 new cases. VL is worsened by malnutrition and HIV co-infection, and it has been suggested that intestinal parasitic infections might also impact on disease severity by modulating cell-mediated immunity and by worsening malnutrition [ 6 ]. Helminth infections are characterised by a strong Th2 response [ 7 ] and it has been suggested that this might suppress a protective Th1 response in VL patients and therefore contribute to the strong immunosuppression characteristic of these patients [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The increasing incidence and spread of HIV/AIDS epidemic has created drastic changes in the society and the economy of nations. Past studies have shown that HIV/AIDS affects people in their productive age groups (15 -49 years old), resulting in a loss of agricultural labour [6]- [9]. In addition, caregivers who have to give up working in the fields in order to take care of the sick deprived labour for agricultural activities [10] [11].…”
Section: Introductionmentioning
confidence: 99%